Cost stickiness: un análisis bibliométrico con agenda para futuras investigaciones - Bubeck, Stephan Klaus (2025)
After the publication of the seminal study by Anderson et al. (2003), several studies have emerged about asymmetric cost behavior, also called cost stickiness. Thus, the present study aimed to carry out a bibliometric analysis of the scientific production on cost stickiness, considering the publications indexed on the Scopus platform between the years 2003 and 2023. The process of filtering the scientific production occurred by type of document, source, language, area of study and theme, which resulted in 213 articles on cost stickiness. Bibliometric analysis was performed with the aid of the Bibliometrix software. The main results indicate a significant increase in publications on the subject from the 2010s onwards, with the United States, China and South Korea being the most productive countries. In addition, authors such as Rajiv Banker and journals such as the Journal of Management Accounting Research stand out both in number of publications and citations. This study serves as a starting point for researchers interested in delving deeper into the literature on cost stickiness, in addition to providing suggestions for future research on the subject.